HUBUNGAN TINGKAT PENGETAHUAN ORANG TUA TENTANG JADWAL PERTUMBUHAN GIGI DENGAN KEJADIAN PERSISTENSI GIGI ANAK 6 – 10 TAHUN DI SDN WOJO I BANTUL - Arie Pratiwi; Siti Sulastri; Siti Hidayati (Poltekkes Kemenkes Yogyakarta, 2014)
Baby teeth guide the permanent teeth emergence roads, in order to occupythe right position in the jaw. Some baby teeth last for 11,5 years from age 6 months to12 years. Age are very susceptible to oral health is a primary school child. The teethare not normally a source of prolonged disruption to dental health. Parents who knowthe period of dental growth both baby teeth and permanent teeth will be very helpful.Based on preliminary studies conducted in the month of February 2012 at SDN WojoI Bantul to assess knowledge of parents about the schedule of events dentition withteeth persistence, 7 of 9 children are children who have persistence and 9 of child’sparents do not know about teething schedule. To determine the relationship gradeparents knowledge about teething schedule with event of teeth persistence children6-10 years old in SDN Wojo I Bantul. Observation used Cross Sectional study design.Population used are 45 children 6-10 years old who have teeth persistence andparents whose children have tooth persistence in SDN Wojo I Bantul. The sampleused amounted to 30 people, a way of sampling is to use a simple sampling of thevote population. The data obtained was made in a cross tabulation then performedstatistical tests using Spearman’s Rank. Knowledge of parents in SDN Wojo I Bantulon teething schedule is mostly good enough to have criteria, which is 70%. Incidenceof child persistence in SDN Wojo I Bantul have most of the criteria for little that isequal to 66,7%, of the total number of respondents. The test statistically results areobtained significant values 0,018 < 0,05 means there is a relationship grade parentsknowledge about teeth schedule with event of teeth persistence children 6-10 yearsold in SDN Wojo I Bantul.